ChemInform Abstract: Transition‐Metal Catalyzed Asymmetric Carbon—Carbon Cross‐Coupling with Chiral Ligands. Issue 46 (27th October 2016) - Yang, He; Yang, Xintong; Tang, Wenjun
Abstract: Review: 118 refs.